Telling Narratives: The Practice of Mapping Space in Pre-Service Art Education Practicum - Sutters, Justin P. (Informática na educação teoria & prática, 2016)
Teacher education programs need to continually adapt to changes in licensure requirements as well as technological advances. This author advances an ethnographic approach to fieldwork that utilizes Google Maps programs to visually represent the collected data and subsequent reflections on their experiences in urban schools. This particular case draws from scholarship in the fields of narrative inquiry, critical cartography and the works of Michel de Certeau to analyze the data collected during the study and draws related implications for the field of art education.